Youngia denticulata attenuates diet-induced obesity-related metabolic dysfunctions by activating AMP-activated protein kinase and regulating lipid metabolism - Kim, Myungsuk; Park, Young Gyun; Lee, Hee-Ju; Lim, Sue Ji; Ahn, Hong Ryul; Jung, Sang Hoon; Nho, Chu Won (ELSEVIER SCIENCE BV, 2015)
Obesity and nonalcoholic fatty liver disease (NAFLD) are characterized by excessive accumulation of triacylglycerol and dysregulation of lipid metabolism. This study investigated the effects of Youngia denticulata extract (YDE) on obesity, hepatic steatosis, inflammation, and antioxidant defences in high-fat diet (HFD)-induced obesity in mice and the molecular mechanisms activated by YDE in HepG2 hepatoma cells. YDE reduced lipid accumulation in HepG2 cells by regulating the expression of lipid metabolism-related enzymes and activating AMP-activated protein kinase (AMPK) signalling. Oral administration of YDE (25 or 100 mg/kg day) to HFD-fed mice lowered the total body weight, adipose and liver tissue weight, insulin resistance, fat deposition, and serum lipids and leptin levels, and augmented the antioxidant enzymes in serum. YDE also altered the expression of lipid metabolism-related enzymes and activated AMPK signalling in liver and white adipose tissue. These results indicate that YDE may be a potent anti-obesity agent. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: FATTY LIVER-DISEASE; INSULIN-RESISTANCE; OXIDATIVE STRESS; HEPATIC LIPOGENESIS; CHLOROGENIC ACID; CAFFEIC ACID; MECHANISMS; STEATOSIS